Breed-specific gut microbiota and enterotype divergence in Chinese indigenous ducks - Wu, Yongfei; Ouyang, Jing; Wang, Luping; Hu, Jingyan; Tang, Hongbo; Zheng, Sumei; Xiong, Yanpeng; Gao, Yuren; Wu, Yan; Xiong, Rui; Huang, Yuxuan; Xuan, Rui; et al. (Frontiers in Microbiology, 2025)
The gut microbiota of domestic ducks plays an important role in digestion and absorption, immune regulation, and overall health. However, our knowledge about the gut microbial composition in ducks of various phylogeny is insufficient, especially if raised in the same farm environment. In this study, 260 fecal samples from 15 Chinese indigenous duck breeds living in a uniformed farm were collected and 16 S rRNA gene sequencing was performed. In addition, 202 blood samples from these ducks were used for whole-genome sequencing (WGS). The WGS results showed that the these domestic duck breeds exhibit breed-specific genetic characteristics. The gut microbiota of different native duck breeds exhibited great similarity at the phylum level with the most dominant phyla being Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes, while harboring distinct gut microbial communities at finer taxonomic levels. The host genetic-specific are associated with the microbial of these duck breeds. The prediction of metagenomic functions showed that the metabolism and function of the gut microbiomes among different duck breeds were more similar than that of their species composition. In addition, Principal coordinates analysis (PCoA) revealed that the gut microbiota of the 15 duck breeds could be divided into two distinct enterotype clusters based on Jensen–Shannon distance (JSD) dissimilarities, with representative breeds corresponding to layer ducks and dual-purpose ducks, respectively. There was no difference in richness index of the gut microbial composition and function between the two enterotypes, but the Shannon index values was significantly different. This study investigated the gut microbial structure and diversity among domestic duck populations with different genetic backgrounds, providing new insights into the relationship between host genetic variation and gut microbiota.